Swine IFN cocktail can reduce mortality and lessen the tissue injury caused by African swine-fever-virus-infected piglets - Jiang, Yitong; Jiang, Fei; Zhai, Wenzhu; Huang, Ying; Pang, Zhongbao; Tao, Chunhao; Wang, Zhen; He, Yuheng; Chu, Yuanyuan; Zhu, Hongfei; Wu, Jiajun; Jia, Hong (Frontiers in Cellular and Infection Microbiology, 2024)
African swine fever (ASF), a highly virulent viral infection, poses a significant threat to the global pig industry. Currently, there are no commercially available vaccines against ASF. While the crucial role of Interferon (IFN) in combating viral infections is well established, its impact on clinical signs and mortality rates of ASF remains unclear. In this study, swine IFN-α2, IFN-γ, and IFN-λ3 were fused with the Fc segment of immunoglobulin G (IgG) and expressed in mammalian cells (293T), which improve the solubility and stability of these recombinant proteins. The specific activities of IFNα2-hFc, IFNγ-hFc and IFNλ3-hFc were determined to be 2.46x10 7 IU/mL, 4.54×10 9 IU/mL and 7.54×10 10 IU/mL, respectively. The IFNs-hFc significantly induced the expression of various IFNstimulated genes (ISGs), including IFIT5, Mx1, OASL, ISG12, STAT1, IRF1, PKR, CXCL10 and GBP1. Furthermore, treatment with the IFN cocktail (a mixture of IFNα2-hFc, IFNγ-hFc and IFNλ3-hFc) reduced the viral load, delayed death, and reduced tissue injury in piglets infected with ASFV. These results suggest that the combined use of the IFN cocktail may be effective in controlling and preventing the onset of ASF.